Alleviating summer stress in dairy cattle through advance housing management - K, Thamothiran; Bharti, P K (Indian Farming, 2018)
Summer stress affects dairy cattle in several ways and finally causes decreased milk production and performance. Important consideration in all the systems should be water economy and recycling. Improved systems capable of either cooling the animal directly or cooling the surrounding environment are necessary for better performance and welfare of dairy animals during summer season.